The physician's unique role in preventing violence: a neglected opportunity? - Umhau, John C; Trandem, Karysse; Shah, Mohsin; George, David T (BMC medicine, 2012)
Episodes of explosive rage and violence comprise a symptom complex which can have a devastating effect on a person's life. In the community this behavior is seen as workplace violence, domestic abuse and road rage, while in the clinical setting, this behavior is rarely mentioned by patients, despite evidence that it can signify an important biological disorder that may afflict more than three percent of the population. Patients are often reluctant to seek help for episodic attacks of rage, especially attacks which are accompanied by physical violence. Although, in the past, clinicians have had few treatment options to offer, recent neuroscience advances have created new possibilities to understand and help patients with this neglected problem. No formal medical guidelines for treating violence exist; however, many patients can be helped by diagnosis, referral and treatment. Treatment can include pharmaceuticals and nutrients, as well as referral for anger management or behavioral therapy. The astute clinician has an opportunity to positively impact an important problem through the diagnosis and treatment of patients with symptoms of intermittent explosive disorder.